A large cross-sectional study on the prevalence and predictors of donor and donation images in patients after heart transplantation - Nora M. Laskowski; Georg Halbeisen; Leoni Wahlers; Katharina Tigges-Limmer; Georgios Paslakis (Scientific Reports)
Abstract Recovery and clinical outcomes following organ transplantation may be negatively influenced by psychological distress. Limited reports from recipients indicate that thoughts and feelings related to the donor/transplanted organ – referred to as donor and donation images (DDI) – may be a source of such distress. The term DDI encompasses all thoughts and emotions that organ recipients associate with the donor or the donated organ. However, empirical knowledge of DDI remains limited. This quantitative survey involving 407 participants represents the first and largest study to quantitatively examine DDI in patients after heart transplantation (HTX). The results revealed a very high prevalence of DDI (91%), with occurrences reported intermittently and often clustered around the time of transplantation, both before and after HTX. Psychological distress predicted the occurrence of DDI before and after HTX and almost all emotions experienced and reported pre-HTX were associated with higher odds of pre-HTX DDI, suggesting it may be a concurrent phenomenon of overall emotional activation. Due to the involvement of emotions associated with uncertainty and low personal control, along with high situational control, DDI may be a part of coping. Some reported avoiding DDI suggesting that, sometimes, they might also represent a stressor. Future studies should further investigate the effects of DDI, including its impact on transplant outcome.